Baseline features and differences in 48 week clinical outcomes in patients with gastroparesis and type 1 vs type 2 diabetes. Issue 7 (6th March 2016) - Koch, K. L.; Hasler, W. L.; Yates, K. P.; Parkman, H. P.; Pasricha, P. J.; Calles‐Escandon, J.; Snape, W. J.; Abell, T. L.; McCallum, R. W.; Nguyen, L. A.; Sarosiek, I.; Farrugia, G.; et al.
Abstract: Background: In studies of diabetic gastroparesis, patients with type 1 and type 2 diabetes mellitus (T1DM, T2DM) are often combined for analyses. We compared gastroparesis severity, healthcare utilization, psychological function, and quality of life in T1DM vs T2DM gastroparesis patients. Methods: Questionnaire, laboratory, and scintigraphy data from patients with gastroparesis and T1DM and T2DM from seven centers of the National Institute of Diabetes and Digestive and Kidney Diseases Gastroparesis Clinical Research Consortium Registry were compared at enrollment and after 48 weeks. Multiple regression models assessed baseline and follow‐up differences between diabetes subtypes. Key Results: At baseline, T1DM patients ( N = 78) had slower gastric emptying, more hospitalizations, more gastric stimulator implantations, higher hemoglobin A1c (HbA1c), and more anxiety vs T2DM patients ( N = 59). Independent discriminators of patients with T1DM vs T2DM included worse gastroesophageal reflux disease, less bloating, more peripheral neuropathy, and fewer comorbidities ( p ≤ 0.05). On follow‐up, gastrointestinal (GI) symptom scores decreased only in T2DM ( p < 0.05), but not in T1DM patients who reported greater prokinetic, proton pump inhibitor, anxiolytic, and gastric stimulator usage over 48 weeks ( p ≤ 0.03). Gastrointestinal symptoms at baseline and 48 weeks with both subtypes were not associated with HbA1c, peripheral neuropathy, psychological factors, or quality of life. Conclusions & Inferences: Baseline symptoms were similar in T1DM and T2DM patients, even though T1DM patients had worse gastric emptying delays and higher HbA1c suggesting other factors mediate symptom severity. Symptom scores at 48 weeks decreased in T2DM, but not T1DM patients, despite increased medical and surgical treatment utilization by T1DM patients. Defining causes of different outcomes in diabetic gastroparesis warrants further investigation. Abstract : This study defined similarities and differences in gastroparesis severity, healthcare utilization, psychological function, and quality of life in patients with type 1 (T1DM) and type 2 (T2DM) diabetes mellitus and gastroparesis. At baseline enrollment, T1DM patients had higher hemoglobin A1c levels and more severe emptying delays, but the severity of GI symptoms was similar to those of patients with T2DM and gastroparesis. After 48 weeks of follow‐up, gastroparesis symptom scores significantly decreased in T2DM patients but not in T1DM patients despite increased use of prokinetic, acid suppressant, anxiolytic, and gastric electrical stimulation therapy in the T1DM group.